2018
DOI: 10.1093/mnras/sty3376
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic localized turbulent diffusion and its impact on the galactic ecosystem

Abstract: Modelling the turbulent diffusion of thermal energy, momentum, and metals is required in all galaxy evolution simulations due to the ubiquity of turbulence in galactic environments. The most commonly employed diffusion model, the Smagorinsky model, is known to be over-diffusive due to its strong dependence on the fluid velocity shear. We present a method for dynamically calculating a more accurate, locally appropriate, turbulent diffusivity: the dynamic localised Smagorinsky model. We investigate a set of stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 121 publications
(225 reference statements)
1
33
0
Order By: Relevance
“…We do note these tests have demonstrated that our default implementation can simultaneously accurately evolve phenomena including gas in regular or warped Keplerian discs, strong interacting shocks, current sheets and flux tubes, supersonic and subsonic turbulence, fluid mixing instabilities (Kelvin-Helmholz, Rayleigh Taylor, etc. ), multifluid dustgas dynamics, collisional+collisionless gravitational dynamics, and reproduces the correct linear growth rates of the magnetorotational instability (MRI) and non-ideal Hall MRI and anisotropic MHD instabilities (magnetothermal, heat-flux-bouyancy) (Hopkins 2015;Hopkins & Raives 2016;Zhu & Li 2016;Lupi, Volonteri & Silk 2017;Deng et al 2019a, b;Moseley et al 2019;Rennehan et al 2019;Hu & Chiang 2020;Panuelos, Wadsley & Kevlahan 2020). Tests of idealized problems involving self-gravitating MHD including the Evrard (1988) problem (spherical collapse of a self-gravitating polytrope), the MHD Zel'dovich (1970) pancake (self-gravitating collapse of an initially linear density perturbation along one dimension in a 3D Hubble flow) demonstrate that the MFM/MFV methods in GIZMO (as well as related moving-mesh methods) converge much more rapidly than popular AMR or SPH methods applied to the same problem (Hopkins 2015;Hopkins & Raives 2016;Hubber, Rosotti & Booth 2018).…”
Section: Existing Testsmentioning
confidence: 80%
“…We do note these tests have demonstrated that our default implementation can simultaneously accurately evolve phenomena including gas in regular or warped Keplerian discs, strong interacting shocks, current sheets and flux tubes, supersonic and subsonic turbulence, fluid mixing instabilities (Kelvin-Helmholz, Rayleigh Taylor, etc. ), multifluid dustgas dynamics, collisional+collisionless gravitational dynamics, and reproduces the correct linear growth rates of the magnetorotational instability (MRI) and non-ideal Hall MRI and anisotropic MHD instabilities (magnetothermal, heat-flux-bouyancy) (Hopkins 2015;Hopkins & Raives 2016;Zhu & Li 2016;Lupi, Volonteri & Silk 2017;Deng et al 2019a, b;Moseley et al 2019;Rennehan et al 2019;Hu & Chiang 2020;Panuelos, Wadsley & Kevlahan 2020). Tests of idealized problems involving self-gravitating MHD including the Evrard (1988) problem (spherical collapse of a self-gravitating polytrope), the MHD Zel'dovich (1970) pancake (self-gravitating collapse of an initially linear density perturbation along one dimension in a 3D Hubble flow) demonstrate that the MFM/MFV methods in GIZMO (as well as related moving-mesh methods) converge much more rapidly than popular AMR or SPH methods applied to the same problem (Hopkins 2015;Hopkins & Raives 2016;Hubber, Rosotti & Booth 2018).…”
Section: Existing Testsmentioning
confidence: 80%
“…where Zi is the mass fraction of a metal in gas element i, and D is the diffusion coefficient. While there is some uncertainty in the exact value to choose for this coefficient, our fiducial value is physically motivated based on tests of the metal diffusion implementation in FIRE-2 on idealized, converged turbulent box simulations by Colbrook et al (2017) and other more extensive studies by Rennehan et al (2019).…”
Section: Appendix C: Impact Of Diffusion Coefficientmentioning
confidence: 99%
“…We can model a small comoving volume of the universe and resolve the galaxies in this volume (e.g. Schaye et al 2015;Pillepich et al 2018;Davé et al 2019) but such volumes generally do not contain the rare massive clusters we would expect to host an object such as SPT2349-56. Or, we can sacrifice resolution in favour of large volumes but then galaxy formation must be introduced in an ad hoc fashion (Ruszkowski & Springel 2009), which can introduce biases.…”
Section: Stellar Assembly and Growthmentioning
confidence: 99%